Rivastigmine prevents injury induced by ischemia and reperfusion in rat liver - Chies,Agnaldo Bruno (2018)
Abstract Purpose: To evaluate whether pre-treatment with rivastigmine is able to attenuate the I/R induced lesions in rat liver. Methods: SHAM animals or those submitted to I/R, non-treated or pre-treated with rivastigminine (2mg/kg) either 50 or 15 minutes before ischemia, were used. After I/R protocol, these animals were killed and their livers were harvested to measurement of the mitochondrial swelling as well as the malondialdehyde (MDA), nitrite and nitrate tissue concentration. Blood was also harvested for serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) determinations. Results: I/R promoted a significant increase of mitochondrial swelling in the studied animals. This increase of mitochondrial swelling was partially prevented by rivastigmine, but only if administered 50 minutes before ischemia. No significant modification of MDA, nitrite or nitrate tissue concentrations was observed in consequence of I/R, followed or not by rivastigmine treatments. In addition, I/R elevated both AST and ALT. These elevations of serum enzymes were not reversed by the different rivastigmine treatments. Conclusions: Rivastigmine administered 50 minutes before ischemia attenuates I/R-induced mitochondrial swelling, that indicates liver injury. This protective effect may be related to a greater stimulation of α7nAChR present in the Kupffer cells by the non-methabolized ACh, leading to an attenuation of I/R-induced inflammation.